STRATEGI PEMASARAN CPO (CRUDE PALM OIL) PADA PT. BIO NUSANTARA TEKNOLOGI BENGKULU TENGAH - Nurzam Nurzam; Efran Ahmat Wijaya (Universitas Muhammadiyah Bengkulu, 2020)
The purpose of this study was to determine how the marketing strategy of CPO (Crude Palm Oil) at PT. Bio Nusantara Teknologi Bengkulu Tengah. Data collection methods used were interviews, documentation and questionnaires. The analytical methods used are SWOT, namely strength, weakness, opportunity and threat. Based on the results of research and data analysis, it can be concluded that the marketing strategy of PT. Bio Nusantara Teknologi Bengkulu Tengah is in quadrant I (first), meaning that PT. Bio Nusantara Teknologi Bengkulu Tengah is a SO strategy, which shows that this business has environmental opportunities and the many forces that encourage the use of these opportunities. This situation suggests a growth oriented strategy (expansion strategy).Keywords: CPO (Crude Palm Oil), SWOT Analysis.